STUDY ON MATURITY AND SPAWNING OF POLYDACTYLUS INDICUS (SHAW) - Karekar, P S; Bal, D V (Indian Journal of Fisheries, 2015)
General survey of the literature on biology of marine fishes of India shows that good deal of work has been done on aspects like food and feeding nabits, development, occurrence, etc. Similarly the study of maturity and spawning activities of fishes of commercial importance has been receiving attention of Indian workers in recent years. Palekar and Karandikar (1950, 1952 and 1953) by using ova diameter as the basis, have roughly demarcated spawning p'riod of Eleutheronema tetradactylum .Shaw), Thrissoclespurava (Ham.) and Coilia dussumieri Cuv. & VaL Contributions of Piabhu (1950, 1955 and 1956) have also supplied useful information on th; maturation of Trichiurus haumela (Forsk.) and several other fishes based mainly on the study of intra-ovarian eggs. Similar investigations carried out by Pradhan (1956) on Mackerel, Sarojini (1957) on Grey Mullet and Krishnamoorthi (1958) on Spotted Seer have helped in determining the extent of the spawning season and fecundity in these fishes.